Asuhan Kebidanan Komprehensif Pada Ny.S Umur 38 Tahun Dengan Faktor Resiko Usia dan Hipertensi Gestasional di Bidan Praktek Mandiri Ny.U Wilayah Kerja Puskesmas Bumiayu Tahun 2023 - Cahyani Wulandari; Himatul Khoeroh; Uma Cholifah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Risk factors during pregnancy can increase complications including gestational hypertension which can contribute to MMR.Maternal mortality according to WHO (2021) is 329,000 people, in Indonesia (2021) there are 7,389 cases, in Central Java (2022) there are 864 cases, in Brebes Regency (2022) there are 50 cases and at the Bumiayu Health Center which is a shade of Brebes Regency also contributes 2 cases. The purpose of this study is to provide midwifery care for pregnant women, maternity, newborns, postpartum and family planning comprehensively. The method in this study used descriptive qualitative with a case study approach. Data collection techniques with interviews, measurements, physical examination and documentation. The main informant is Mrs. S with additional informants namely husband, family, midwife and Dr. Sp.OG. Based on the results of pregnancy, childbirth, newborn, postpartum and family planning. Found problems during pregnancy, namely Mrs. S with blood pressure 140/103 mmHg, negative urine protein which is classified as gestational hypertension.